2013
DOI: 10.1097/ccm.0b013e3182982add
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Necrosis Factor Therapy Is Associated With Improved Survival in Clinical Sepsis Trials

Abstract: Background Sepsis is a lethal syndrome annually affecting ~900,000 patients in the United States alone. Despite their benefit in rheumatoid disease, selective anti-tumor necrosis factor (anti-TNF) agents failed to improve outcome in early sepsis trials in the 1990’s. However, data from additional sepsis trials testing these agents is now available. Purpose To determine the effect on survival of selective anti-TNF agents in randomized clinical sepsis trials. Data Sources PubMed, Scopus, EMBASE, and Web of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 30 publications
3
62
0
1
Order By: Relevance
“…Many of the initial trials of anti-TNF in sepsis found no significant change in the mortality rates but they may have been underpowered. A recent meta-analysis has shown a small but significant reduction in mortality with anti-TNF among patients with sepsis 19. These clinical trials were looking at the benefit of giving a single dose of anti-TNF to patients who already had developed sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the initial trials of anti-TNF in sepsis found no significant change in the mortality rates but they may have been underpowered. A recent meta-analysis has shown a small but significant reduction in mortality with anti-TNF among patients with sepsis 19. These clinical trials were looking at the benefit of giving a single dose of anti-TNF to patients who already had developed sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical efficacy of anti-TNF-α therapy remains disputed, there is some evidence that it may reduce the number of days of mechanical ventilation and days in the intensive care unit in patients with severe sepsis [38]. Two meta-analyses also demonstrated that anti-TNF-α therapy is associated with a significant decrease in sepsis-related mortality [39,40]. A large, multicenter randomized follow-up trial may be warranted to confirm these benefits and to evaluate the incidence of drug-related side effects.…”
Section: The Cytokine Storm and Sepsismentioning
confidence: 99%
“…After “successfully” executing various treatments (i.e., against circulating cytokines or endotoxins) in the mouse (98), rat (102), rabbit (103), dog (104) and non-human primates (105), the striking failure of similar anti-inflammatory therapeutic protocols in septic patients has brought a painful realization that injecting mice and other species with a lethal dose of bacterial LPS is not a good predictive model for a typical human sepsis. It must be stressed, however, that a complete renouncement of anti-inflammatory treatments based on the failed trials would be equally short sighted and the most recent meta-analysis argues that application of anti-TNF agents in septic patients should be revisited (106). It has become clear that responses elicited in sepsis are highly mixed and the immunosuppressive component frequently exceeds hyperinflammation (107).…”
Section: The Good and The Bad: The Role Of Mouse Models In Critical Imentioning
confidence: 99%